INTERPRETING STRATEGIES ANALYSIS IN THE CHINESE-ENGLISH SIMULTANEOUS INTERPRETATION VIDEO CLIPS - Ma, Ling; Junining, Esti; Hariyanto, Sugeng (Erudio Journal of Educational Innovation, 2025)
ABSTRACTThis article aims to enhance the understanding of strategic competence in the field of interpreting. Following a concise examination of the primary contributions related to the concept of strategies in interpreting, the article presents a study that scrutinises the strategies employed by two students in interpreting. This study aims to simultaneous interpreting strategies used by the student interpreters when doing the video simultaneous interpreting. The data source is the Chinese to English simultaneous interpreting video record in the subject speech of Run Liu’s The Power of Evolution done by the student interpreters Selena_jm and Wenchao Liu on 12th November 2023. The results of the study revealed there were three interpreting strategies employed by the simultaneous interpreting from Chinese to English in the video clip of Run Liu’s speech The Power of Evolution. The strategies employed by the interpreter include Generalization (33.33% & 90%), omission (66.66%), and paraphrasing (9%).